KAJIAN SIMPANAN KARBON PADA BIOMASSA MANGROVE DI PESISIR DESA TATENGESAN KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA PROVINSI SULAWESI UTARA - Tirsa Lumbu; Antonius P. Rumengan; Carolus P. Paruntu; Suria Darwisito; Medy Ompi; Stephanus Mandagi (Sam Ratulangi University, 2022)
Mangroves are referred to as coastal forests or brackish forests, coastal forests which mean forests that live in coastal areas (coastal) which are influenced by tidal areas and coastal land. Mangroves have an important role in the absorption and storage of carbon, the amount of carbon contained in a tree is influenced by the ability of the tree to absorb carbon from the environment by the process of photosynthesis or known as the sequestration process. The purpose of this study was to identify the types of mangroves on the coast of Tatengesan and determine the carbon storage in the biomass of mangrove trees on the coast of Tatengesan. Data collection on mangrove tree vegetation was carried out in 3 transects, on the left, right and middle of the mangrove ecosystem on the Tatengesan coast. The transects were drawn perpendicular from the sea to the coast according to the thickness of the mangroves at the site. One transect has three quadrants, with a size of 10 m x 10 m. For how it works, the transect is pulled 100 m from the sea to the beach, then the quadrants are measured 10 m x 10 m using a plastic rope as a marker, and the quadrant positions are placed randomly and for 25 m intervals. The results of this study provide information that there are 3 types of mangroves, namely Rhizophora apiculata, Rhizophora mucronata, and Bruguiera gymnorhiza, the value of mangrove biomass content ranges from 69.2 - 118.61 tons/ha, and the value of carbon storage in mangrove biomass. ranged from 32.52 to 55.75 tons/ha. Future research is expected to obtain time series data on the amount of carbon stored in a certain time period. Keywords: Biomass, carbon, mangrove, Tatengesan ABSTRAK Mangrove disebut sebagai hutan pantai atau hutan payau, hutan pantai yang berarti hutan yang hidup di daerah pantai (pesisir) yang dipengaruhi oleh daerah pasang surut air laut dan daratan pesisir. Mangrove memiliki peranan penting dalam hal penyerapan dan penyimpanan karbon, besarnya kandungan karbon yang terdapat dalam satu pohon dipengaruhi oleh kemampuan pohon tersebut untuk menyerap karbon dari lingkungan dengan proses fotosintesis atau yang dikenal dengan proses sequestration. Tujuan dari penelitian ini adalah untuk mengidentifikasi jenis-jenis mangrove di pesisir Tatengesan dan mengetahui simpanan karbon pada biomassa pohon mangrove di pesisir Tatengesan. Pengambilan data pada vegetasi pohon mangrove dilakukan sebanyak 3 transek, pada bagian kiri, kanan dan tengah ekosistem man grove di pesisir Tatengesan. Transek ditarik tegak lurus dari arah laut ke pantai sesuai ketebalan mangrove di lokasi. Satu transek terdapat tiga kuadran, dengan ukuran 10 m x 10 m. Untuk cara kerjanya, transek ditarik sejauh 100 m dari laut ke pantai, kemudian kuadran diukur 10 m x 10 m dengan menggunakan tali plastik sebagai penanda, dan untuk posisi kuadran diletakkan acak dan untuk intervalnya 25 m. Hasil penelitian ini memberikan informasi bahwa jenis-jenis mangrove ditemukan sebanyak 3 jenis, yaitu Rhizophora apiculata, Rhizophora mucronata, dan Bruguiera gymnorhiza, nilai kandungan biomassa mangrove berkisar antara 69,2 – 118,61 ton/ha, dan nilai simpanan karbon pada biomassa mangrove berkisar antara 32,52 – 55,75 ton/ha. Penelitian selanjutnya diharapkan untuk memperoleh data time series jumlah simpanan karbon dalam suatu periode waktu tertentu. Kata kunci: Biomassa, karbon, mangrove, Tatengesan